Ethno-artistic constants of the image of the child in the works of contemporary Tuvan writers A. Lamazhaa and Ch. Kuular - Garipova, Gulchira T.; Zharbulova, Saule T.; Shafranskaya, Eleonora F. (The New Research of Tuva, 2026)
The article examines the principles and ways of depicting the image of the child in contemporary Tuvan literature, using the works of A. Lamazhaa and Ch. Kuular as examples. In the process of artistic representation of the child’s image, the writers correlate it with ethnic correlates that go back not only to the everyday world, but also to ritual traditions and to the historical realities of the life of the Tuvan people.Artistic works in which the main character is a child expressing the author’s worldview position represent ethnocultural and universal mythological, existential and ontological value axioms. The child character, as the author’s alter ego, projects a particular understanding of the ethnic culture of childhood, associated both with tradition and with universal values, which determine the ethno-artistic constants of its subjective structure.The study identifies axiologemes (home, family, land) that are represented through direct nominations and signs (symbols, archetypes) of Tuvan ethnoculture, which serve as markers of the idea of generational continuity in the works under analysis. It is revealed that in the prose of A. Lamazhaa and Ch. Kuular the concept of “ancestral memory” structures the “children’s world” model through a system of traditional values and rituals of Tuvan ethnoculture, forming the ethno-artistic constants of the child’s image. In their works, the child is presented as an active subject of national existence, a mediator of ethnocultural tradition, a bearer of the collective experience of the Tuvans, and an exponent of the author’s existential consciousness.
Keywords: image of the child; ancestral memory; continuity of generations; sacred; mythopoetics; Tuvans; Tuvan literature; Tuvan culture; culture of childhood; Anna Mombuzhaevna Lamazhaa; Cherlig-ool Chashkynmaevich Kuular